The Mitridae (Gastropoda: Neogastropoda) of the Miocene Paratethys Sea - Harzhauser, Mathias; Landau, Bernard (Zootaxa, 2021)
The gastropod family Mitridae in the Miocene Paratethys Sea is revised. In total, 35 species in eight genera are reported. 75% of the species are so far known only from the Paratethys Sea. Biogeographic relations with the adjacent Proto-Mediterranean Sea are moderate and are mainly documented within Cancilla, but nearly absent in the other genera. A slight South-North trend in diversity is observed within the Paratethyan basins, with an outstandingly high diversity of 22 species in the Romanian Făget Basin, but only nine species in the Polish and Ukrainian parts of the Fore-Carpathian Basin.                Fraudiziba nov. gen. and Wormsina nov. gen. are introduced as new genera. Twelve species are described as new: Episcomitra antibellardii nov. sp., Episcomitra leopoldiana nov. sp., Episcomitra pseudoincognita nov. sp., Episcomitra missile nov. sp., Episcomitra neubaueri nov. sp., Domiporta amoena nov. sp., Domiporta pulchra nov. sp., Domiporta turpis nov. sp., Nebularia soliphila nov. sp., Cancilla nanostriatula nov. sp., and Cancilla wagreichi nov. sp. Fraudiziba ottomanica nov. sp. is described as new species from the middle Miocene of the Karaman Basin in Turkey.                Lectotypes are designated for M. austriaca Csepreghy-Meznerics, 1950, Mitra brusinai Hoernes & Auinger, 1880, M. cochlearella Mayer-Eymar, 1890, M. friedbergi Cossmann, 1912, Mitra hoernesi Mayer, 1864, Mitra perangulata Peyrot, 1928, M. praenigra Mayer-Eymar, 1890, and Mitra transsylvanica Hoernes & Auinger, 1880. Fraudiziba paratethyca nov. nom. is proposed as new name for Mitra austriaca Csepreghy-Meznerics 1950 [non Mayer-Eymar, 1898].